Obstructive Sleep Apnea and Chronic Obstructive Pulmonary Disease Overlap Syndrome - Marin-Oto, Marta; Sanz-Rubio, David; Marin, José M. (Seminars in Respiratory and Critical Care Medicine, 2025)
The coexistence of chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) in the same patients is defined as COPD/OSA overlap syndrome (OVL). OSA and sleep complaints are quite common among COPD patients and contribute to an increase in the risk of COPD exacerbation and mortality. Patients with OVL are more likely to develop cardiometabolic disease than patients with OSA or COPD alone. We must consider OSA as a treatable trait since the use of positive pressure ventilation reduces severe exacerbations, all-cause hospitalizations, and mortality in patients with COPD.
Keywords: chronic obstructive pulmonary disease; obstructive sleep apnea; overlap syndrome; positive pressure ventilation